Joint Charge Storage for High‐Rate Aqueous Zinc–Manganese Dioxide Batteries - Jin, Yan; Zou, Lianfeng; Liu, Lili; Engelhard, Mark H.; Patel, Rajankumar L.; Nie, Zimin; Han, Kee Sung; Shao, Yuyan; Wang, Chongmin; Zhu, Jia; Pan, Huilin; Liu, Jun (Advanced materials (Weinheim), 2019)
Aqueous rechargeable zinc–manganese dioxide batteries show great promise for large‐scale energy storage due to their use of environmentally friendly, abundant, and rechargeable Zn metal anodes and MnO2 cathodes. In the literature various intercalation and conversion reaction mechanisms in MnO2 have been reported, but it is not clear how these mechanisms can be simultaneously manipulated to improve the charge storage and transport properties. A systematical study to understand the charge storage mechanisms in a layered δ‐MnO2 cathode is reported. An electrolyte‐dependent reaction mechanism in δ‐MnO2 is identified. Nondiffusion controlled Zn2+ intercalation in bulky δ‐MnO2 and control of H+ conversion reaction pathways over a wide C‐rate charge–discharge range facilitate high rate performance of the δ‐MnO2 cathode without sacrificing the energy density in optimal electrolytes. The Zn‐δ‐MnO2 system delivers a discharge capacity of 136.9 mAh g−1 at 20 C and capacity retention of 93% over 4000 cycles with this joint charge storage mechanism. This study opens a new gateway for the design of high‐rate electrode materials by manipulating the effective redox reactions in electrode materials for rechargeable batteries. Rational manipulation of the charge‐storage mechanism of aqueous rechargeable Zn–MnO2 batteries is demonstrated through the use of a layered δ‐MnO2 cathode. Nondiffusion control of pseudocapacitance‐like Zn2+ intercalation in bulky δ‐MnO2, followed by control of the H+ conversion reaction pathway over a wide C‐rate charge–discharge range facilitates high rate and a long lifetime of δ‐MnO2 cathodes.